PENERAPAN RESTORATIVE JUSTICE TERHADAP PELAKU TINDAK PIDANA PENCURIAN - Sihombing, Janter83 (Yayasan Tri Edukasi Ilmiah, 2025)
Restorative Justice is the resolution of criminal acts involving the perpetrator, victim, family, community leaders, or stakeholders to jointly seek a just resolution through peace with an emphasis on restoring the situation to its original state. Settlement using the application of Restorative Justice itself is regulated in National Police Regulation No. 8 of 2021 concerning the handling of criminal acts based on restorative justice. In this study, the author explores how Restorative Justice is implemented in the jurisdiction of the Pangkalan Kuras Police, Pelalawan Regency, Riau, specifically in cases of theft. Many of the theft cases encountered are minor thefts, for example, theft of oil palm fruit, with victims being individuals and companies. The resolution of these crimes can still be resolved through amicable means between the perpetrator and the victim, whether an individual or a company, accompanied by community members recognized as regional stakeholders in their respective regions.